Aplicación móvil para el seguimiento de actividades académicas de los estudiantes de la Unidad Educativa Fiscal Patria Provincia de Cotopaxi. - Lozada Maldonado, Ana Cristina (2017)
In the Patria Fiscal Education Unit there are specific schedules where teachers provide tutoring to parents, and it is difficult for them to approach the institution for various reasons, in search of each teacher to obtain knowledge about the academic activities carried out by their children Therefore the present project proposes to develop a mobile application that allows to monitor the academic activities of the students of the Fiscal Education Unit Patria province of Cotopaxi by means of notifications in real time to the parents. The motivation of this proposal to contribute to the process of communication of the teachers with the parents and thus to know the academic activities of the students in real time of the institution. The bibliographic information gathered in several sources such as scientific articles, theses, books and online sources is detailed in the theoretical basis. These bibliographic sources are listed in the respective section of this document. For the development of the mobile application the methodologies that have been used are directed to the systems area; was taken as a Mobile-d development model guide for the mobile part, and Scrum for the Web part.Within the research methodology has been used instruments such as: survey and interview the same that is addressed to teachers and parents of the institution. At the moment of the implementation and training of the users could be observed the acceptance before the mobile application.